Using a flux-driven simulation to capture marginality in plasma turbulence - Khoo, Le Han (Nanyang Technological University, 2024)
On the path towards energy breakeven in nuclear fusion reactors, great amounts of research have also been invested in computational physics to create simulations that allow for the simulation of the plasma conditions within a tokamak; but there is still much more work to be done to create a reduced element model that can run within reason- able computational resources and timeframes. We will describe one such program - GYSELA, a flux-based global gyrokinetic code. Additionally, we will characterize the difference between its flux-driven model and gradient-driven models, the evolution of turbulent transport barriers in plasma and the ongoing research to synergize both mod- els. We also present our results in GYSELA that describe the near-marginal conditions that allow for turbulent transport barrier formation, demonstrate the formation of E x B staircases and suppression of turbulence.